Studi Kasus Asuhan Keperawatan Keluarga Pada Klien Ny. H Dengan Diagnosis Gastritis - Aisyah, Nur; SUdarta, I Made; Hasir, Hasir (Jurnal Keperawatan Majampangi, 2026)
Gastritis is one of the most common non-communicable diseases in the community and may interfere with daily activities if not properly managed. This case study aimed to implement family nursing care for Mrs. H, a member of Mr. S's family, who was diagnosed with gastritis. A case study design was employed using the family nursing care approach, which included assessment, nursing diagnosis, intervention, implementation, and evaluation. The study identified three nursing diagnoses: acute pain, ineffective family health management, and readiness for enhanced family coping. Nursing interventions were carried out over a three-day period using health education and deep breathing relaxation techniques. The evaluation demonstrated a reduction in pain complaints, improved family understanding of gastritis management, and enhanced family capability in providing care for the client. Family nursing care was effective in supporting the recovery process of gastritis and increasing family involvement in home-based care. Continuous assistance and follow-up support from the community health center should be provided to families with members suffering from gastritis